Epidemiology, natural history, progression, and postnatal outcome of severe fetal ventriculomegaly - Hannon, Therese; Tennant, Peter W G; Rankin, Judith; Robson, Stephen C (Obstetrics and gynecology (New York. 1953), 2012)
To estimate the prevalence, associated anomalies, progression, and clinical outcome in fetuses prenatally diagnosed with severe ventriculomegaly. This is a population-based study using prospectively collected data from the north of England. Data were obtained from the Northern Congenital Abnormality Survey for the period 1994-2008. Associated anomalies were categorized using the European Surveillance of Congenital Anomalies guidelines. Differences between isolated and nonisolated ventriculomegaly were examined using Fisher's exact test or Mann-Whitney U test. There were 157 cases of confirmed severe ventriculomegaly in singleton pregnancies among 441,247 eligible births, a prevalence of 3.6 per 10,000 births (95% confidence interval [CI] 3.0-4.2). Chromosomal anomalies were detected prenatally in five cases (3.2%, 95% CI 1.0-7.3) and associated structural anomalies in 67 (42.7%, 95% CI 34.8-50.8). One hundred one women (64.3%) elected to have a termination of pregnancy, more commonly in the presence of associated anomalies (76.9% compared with 51.9%, P=.001). Ultrasonographic follow-up data were available for 53 fetuses; in 13 cases (24.5%), atrium size decreased prenatally, whereas in the remainder, median atrium size increased by 4.1 mm over 3.5 weeks. Associated anomalies were detected postnatally in 22 of 79 cases suspected prenatally to be isolated (27.8%, 95% CI 18.3-39.1). Of 53 live births, there were 11 (20.8%) neonatal deaths, including six (16.2%) of the isolated group. Neonatal death was not predicted by atrial measurement progression. The prevalence of severe ventriculomegaly was 3.6 per 10,000 births. Although more than 50% opt to terminate, of those with live births, there were 21% neonatal deaths with nearly half in neonates with isolated ventriculomegaly.